Comparison of DNA Extraction Feasibility from Menstrual Blood and Endometrial Tissue in Reproductive-Aged Women - Febriyeni; Hestiantoro, Andon; Asmarinah; Tulandi, Togas; Hasnita, Evi; Zuraida; Harnaldo Putra, Billy; Octariyana; Rizki Amanda, Clara; Astria Rishel, RIka (LPPM Universitas Prima Nusantara Bukittinggi, 2025)
ABSTRACT The endometrium is a highly vascularized tissue composed of numerous blood vessels, with cells that are formed and destroyed during each menstrual cycle. Menstrual blood, which is shed cyclically from the endometrium in women of reproductive age, contains endometrial tissue or cells. Both deoxyribonucleic acid (DNA) and ribonucleic acid (RNA) are the primary nucleic acids present in cells with nuclei. In this study, 20 samples of menstrual blood and endometrial tissue were collected from women of reproductive age. Menstrual blood was gathered using specially designed filter paper, and DNA was extracted using the QIAamp DNA Mini Kit (Qiagen, Cat No.: 51304). Endometrial tissue was obtained via biopsy, and DNA was extracted using the Geneaid DNA Isolation Kit (Geneaid, New Taipei, Taiwan). DNA purity and concentration were measured using a Thermo Scientific Nano-Drop microvolume Spectrophotometer. The results indicated an average DNA purity of 1.88 ± 0.09 and a mean concentration of 116.9 ng/µL for menstrual blood, while endometrial tissue had a median DNA purity of 1.92 and a concentration of 192 ng/µL. Statistical analysis revealed no significant difference in DNA purity between menstrual blood and endometrial tissue (p = 0.083), but a significant difference in DNA concentration was observed (p = 0.002). Although there was a slight difference in DNA concentration, both menstrual blood and endometrial tissue samples were equally effective in preserving optimal purity and concentration of DNA molecules. Keywords: Deoxyribonucleic Acid, DNA, Endometrial Tissue, Menstrual Blood, Nucleic Acid.